2018
DOI: 10.1063/1.5041496
|View full text |Cite
|
Sign up to set email alerts
|

Two-fluid solutions for Langmuir probes in collisionless and isothermal plasma, over all space and bias potential

Abstract: This paper presents solutions for the classical one-dimensional (radial and Cartesian) problem of Langmuir probes in a collisionless, isothermal plasma. The method is based on two-fluid equations derived from the first two moments of Vlasov's equation. In contrast to commonly-used approximations, electron inertia and ion temperature are not neglected so that the fluid equations are symmetric in the terms for electrons and ions. The fluid equations are reduced analytically so that the electric potential is the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(22 citation statements)
references
References 44 publications
4
18
0
Order By: Relevance
“…6 In this Brief Communication, it is shown that the Lambert function is in fact a general solution for onedimensional, isothermal compressible fluid equations in classical fluid dynamics. The analogy with fluid dynamics gives physical insight into the Lambert solution, and confirms the intuitive assumptions for the fluid boundary conditions in [5].…”
supporting
confidence: 63%
See 4 more Smart Citations
“…6 In this Brief Communication, it is shown that the Lambert function is in fact a general solution for onedimensional, isothermal compressible fluid equations in classical fluid dynamics. The analogy with fluid dynamics gives physical insight into the Lambert solution, and confirms the intuitive assumptions for the fluid boundary conditions in [5].…”
supporting
confidence: 63%
“…Langmuir probes are one of the most fundamental diagnostics of plasma physics. [1][2][3][4] A recent paper 5 presented a mathematical treatment for radial Langmuir probes in collisionless, isothermal plasma by using the Lambert function. 6 In this Brief Communication, it is shown that the Lambert function is in fact a general solution for onedimensional, isothermal compressible fluid equations in classical fluid dynamics.…”
mentioning
confidence: 99%
See 3 more Smart Citations